2015
DOI: 10.1016/j.ijmyco.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycobacterium tuberculosis LAM family in the worldwide population: A systematic review and meta-analysis

Abstract: Background: Transmission of Mycobacterium tuberculosis ( M. tuberculosis ) can occur in different ways. Furthermore, drug resistant in M. tuberculosis family is a major problem that creates obstacles in treatment and control of tuberculosis (TB) in the world. One of the most prevalent families of M. tuberculosis is Haarlem, and it is associated with drug resistant. Our objectives of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…The following data were extracted from original publications: a number of cases, websites, author, study location, year of the research, sample size, prevalence of embB 306, and occurrence of mutations (yes or no). [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following data were extracted from original publications: a number of cases, websites, author, study location, year of the research, sample size, prevalence of embB 306, and occurrence of mutations (yes or no). [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
“…Excluded studies were as follows: 1) review and meta-analysis articles; 2) congress abstracts; 3) studies that were in languages other than English (abstract in English was acceptable); 4) studies that were not available for the authors in abstract or full-text; 5) studies that their sampling location and time of the study was unclear; 6) studies that were performed at the location of sampling and immediately after it; 7) studies that their data were not clear; and 8) letters to editors. [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Haarlem sub-lineage has been linked with drugresistance and clonal expansion (Ramazanzadeh et al, 2015). We found that in "Papaloapan" region two of the three Haarlem isolates characterized were resistant to all drugs tested, in contrast with the isolates belonging to "Mixteca" region that were pan-susceptible.…”
Section: Discussionmentioning
confidence: 79%